A 29-Year-Old Man with Hospital-Acquired Cavitary Pneumonia - Mansoor Mehmood; Ruba A Halloush; Faisal A Khasawneh (Canadian Respiratory Journal)
Mucormycosis is an infection that can manifest in many forms and is an emerging complication in several health care procedures. Portals of entry can be attributed to surgical procedures and medical devices such as chest tubes; however, the skin and gastrointestinal tract are the most common sites of infection and outbreaks have been traced to adhesive bandages, wooden tongue depressors and ostomy bags. This article describes the presentation, work-up, diagnosis and treatment of an East Asian immigrant who was admitted with acute hypoxemic respiratory failure.